American Society of Anesthesiologists physical status score as a predictor of long-term outcome in women with endometrial cancer. Issue 5 (20th March 2019) - Kolehmainen, Anne Maarit; Pasanen, Annukka; Tuomi, Taru; Koivisto-Korander, Riitta; Butzow, Ralf; Loukovaara, Mikko
Abstract : Objective: To study the association of the American Society of Anesthesiologists (ASA) physical status score with long-term outcome in endometrial cancer. Methods: Overall, disease-specific and non-cancer-related survival were estimated using simple and multivariable Cox regression analyses and the Kaplan-Meier method. Results: A total of 1166 patients were included in the study. Median follow-up time was 76 (range 1–136) months. All-cause and non-cancer-related mortality were increased in patients whose ASA physical status score was III (HRs 2.5 and 8.0, respectively) or IV (HRs 5.7 and 25, respectively), and cancer-related mortality was increased in patients whose score was IV (HR 2.7). Kaplan-Meier analyses demonstrated a worse overall, disease-specific and non-cancer-related survival for patients whose score was ≥III (p<0.0001 for all). Disease-specific survival was also separately analyzed for patients with stage I and stage II–IV cancer. Compared with patients whose score was ≤II, the survival was worse for patients whose score was ≥III in both subgroups of stages (p=0.003 and p=0.017 for stage I and stages II–IV, respectively). ASA physical status score remained an independent predictor of all-cause mortality (HR 2.2 for scores ≥III), cancer-related mortality (HRs 1.7 and 2.2 for scores ≥III and IV, respectively) and non-cancer related mortality (HR 3.1 for scores ≥III) after adjustment for prognostically relevant clinicopathologic and blood-based covariates. ASA physical status score also remained an independent predictor of cancer-related mortality after exclusion of patients who were at risk for nodal involvement based on features of the primary tumor but who did not undergo lymphadenectomy, and patients with advanced disease who received suboptimal chemotherapy (HRs 1.6 and 2.5 for scores ≥III and IV, respectively). Conclusions: ASA physical status score independently predicts overall survival, disease-specific survival, and non-cancer-related survival in endometrial cancer.